Periglacial geomorphology in the 21st century - Barsch, Dietrich (Geomorphology, 1993)
Periglacial geomorphology, defined in a classical manner, experiences at the moment a strong development. Nevertheless, there remain weaknesses which are often derived from the fact that the clear laws of physics are seldom fully applied in the open, non-isolated systems under discussion. In the next century, important tasks in periglacial geomorphic research are the development of a better understanding •-of the physical nature of periglacial processes,•-of the relationships between periglacial processes and landforms,•-of former, present, and of future periglacial environments based on reliable models. The future of periglacial geomorphology is exciting, because it has to predict the environmental changes which occur in high-latitude and high-altitude periglacial geosystems if the present models of climatic changes are correct. This provides challenging possibilities for broad-scale geomorphic prediction and experimentation.
Elektronische Reproduktion der Druck-Ausgabe 9. April 2003
Gesehen am 20.02.2023